PERBAIKAN METODE KERJA UNTUK MENINGKATKAN EFEKTIVITAS DAN EFESIENSI PADA PEMELIHARAAN JARINGAN DISTRIBUSI TENAGA LISTRIK - I G. Wahyu A.K; I Made Budiada; I Gusti Ketut Abasana; I Nym. Sugiarta (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
In a global era like today, the use of electrical energy is undeniable, almost every work done is related to electricity. In order to ensure the distribution of electrical energy remains in a reliable condition, a good system is needed to support the distribution of electricity. Maintenance work and countermeasures of disturbances in the power distribution network are among the factors that must be carried out to ensure the quality and continuity of the distribution of electrical energy from power providers to load centers. With the demands of this task, every unit under the auspices of PT. PLN (Persero), especially the Java-Bali area, is required to have a good work system design in serving customers, a planned distribution network maintenance work program and fast disruption management. To achieve the demands of such a heavy task, almost all units carry out work management on the power grid consistently, but in its implementation is not balanced with attention to effectiveness, comfort, safety and work efficiency. This condition does not only occur in Bali or Indonesia, but also in developed countries so more serious attention is needed to improve conditions like this by implementing good work management. For this reason, corrective action is needed, including through improving work methods in improving conditions and ways of working that are able to build a safe, comfortable, healthy, effective and efficient work culture to increase work productivity, so that the welfare and quality of life of workers increases.